Adverse drug reactions in hospitalised children in Germany are decreasing: results of a nine year cohort-based comparison. - Ann-Kathrin Oehme (Public Library of Science (PLoS), 2012)
Background In recent years, efforts have been made to improve paediatric drug therapy. The aim of this research was to investigate any changes regarding the frequency and nature of adverse drug reactions (ADRs) in hospitalized children in one paediatric general medical ward over a 9-year period. Methodology Two prospective observational cohort studies were conducted at a large University hospital in Germany in 1999 and 2008, respectively. Children aged 0-18 years admitted to the study ward during the study periods were included. ADRs were identified using intensive chart review. Uni- and multivariable regression has been used for data analysis. Results A total of 520 patients (574 admissions) were included [1999: n = 144 (167); 2008: n = 376 (407)]. Patients received a total of 2053 drugs [median 3, interquartile range (IQR) 2-5]. 19% of patients did not receive any medication. Median length of stay was 4 days (IQR 3-7; range 1-190 days) with a significantly longer length of stay in 1999. The overall ADR incidence was 13.1% (95% CI, 9.8-16.3) varying significantly between the two study cohorts [1999: 21.9%, 95% CI, 14.7-29.0; 2008: 9.2%, 95% CI, 5.9-12.5 (p<0.001)]. Antibacterials and corticosteroids for systemic use caused most of the ADRs in both cohorts (1999; 2008). Exposure to systemic antibacterials decreased from 62.9% to 43.5% whereas exposure to analgesics and anti-inflammatory drugs increased from 17.4% to 45.2%, respectively. The use of high risk drugs decreased from 75% to 62.2%. In 1999, 45.7% and in 2008 96.2% of ADRs were identified by treating clinicians (p<0.001). Conclusions Between 1999 and 2008, the incidence of ADRs decreased significantly. Improved treatment strategies and an increased awareness of ADRs by physicians are most likely to be the cause for this positive development. Nevertheless further research on ADRs particularly in primary care and the establishment of prospective pharmacovigilance systems are still needed.